2012
DOI: 10.1111/j.1471-0528.2012.03397.x
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of low to moderate alcohol consumption and binge drinking in early pregnancy on executive function in 5‐year‐old children

Abstract: Please cite this paper as: SkogerbøÅ, Kesmodel U, Wimberley T, Støvring H, Bertrand J, Landrø N, Mortensen E. The effects of low to moderate alcohol consumption and binge drinking in early pregnancy on executive function in 5‐year‐old children. BJOG 2012;119:1201–1210. Objective  To examine the effects of low to moderate maternal alcohol consumption and binge drinking in early pregnancy on children’s executive functions at the age of 5 years. Design  Follow‐up study. Setting  Neuropsychological testing in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 36 publications
6
58
0
2
Order By: Relevance
“…Multivariate analysis showed no statistically significant effects of average weekly alcohol consumption, either individually or in combination on child's intelligence, attention and executive function [36]. These results replicate findings from separate analyses of alcohol consumption on child's intelligence, attention and executive function [31,35]. In summary, more compelling and stronger evidence is needed to evaluate the effect of low-to-moderate levels drinking during pregnancy.…”
Section: Criteria For Inclusion Of Studies Into the Reviewsupporting
confidence: 71%
See 2 more Smart Citations
“…Multivariate analysis showed no statistically significant effects of average weekly alcohol consumption, either individually or in combination on child's intelligence, attention and executive function [36]. These results replicate findings from separate analyses of alcohol consumption on child's intelligence, attention and executive function [31,35]. In summary, more compelling and stronger evidence is needed to evaluate the effect of low-to-moderate levels drinking during pregnancy.…”
Section: Criteria For Inclusion Of Studies Into the Reviewsupporting
confidence: 71%
“…A Taiwanese cohort study reported a negative association between cotinine levels and 2-year child neurodevelopment assessed by developmental quotients of the whole test and cognitive, language, fine motor and social subtests of the Comprehensive and measures of self-control [33]. Skogerbøet al (2012) did not observe significant effects of low and moderate alcohol consumption during pregnancy on executive functioning at 5 years of age among children from the Danish National Birth Cohort [31]. The next group of the studies is associated with the children IQ measures.…”
Section: Criteria For Inclusion Of Studies Into the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…All rights reserved during pregnancy) and neurodevelopmental outcomes among their 5-year-old children. Previous analyses from this dataset have been reported elsewhere for intelligence (Falgreen Eriksen et al, 2012;Kesmodel et al, 2012b), attention (Underbjerg et al, 2012), executive functioning (Skogerbø et al, 2012) and behavioral problems (Skogerbø et al, 2013). Findings indicated negative effects for children of women drinking 9 or more drinks per week.…”
Section: Introductionmentioning
confidence: 77%
“…Executive functioning is a complicated construct that encompasses a series of cognitive processes such as planning (Kalberg & Buckley, 2007;Skogerbø et al, 2012), inhibition, working memory, and task switching (Davis, Gagnier, Moore, & Todorow, 2013). It also includes behavioral skills such as "sequencing behavior to efficiently achieve a goal" (Kalberg & Buckley, 2007, p.279), measures of self-control (Skogerbø, et al, 2012), and using stimulus-reward associations to serve the plan for problem solving (Davis et al, 2013). Overall, executive functioning has been recognized as a central deficit for individuals with FASD (Kodituwakku, 2009;Mattson, Riley, Gramling, Delis, & Jones, 1998;Rasmussen, 2005;).…”
Section: Cognitive Developmentmentioning
confidence: 99%